Lycium ruthenicum Murr. treatment attenuates APPswE/PS1ΔE9 mouse model-like mitochondrial dysfunction in Slc25a46 knockout mouse model - Min Wang; Tianxiong Xu; Li Gao; Chujun Huang; Piao Xu; Congcong Gong; William Kwame Amakye; Linfeng Liao; Maojin Yao; Jiaoyan Ren (Food Science and Human Wellness)
Mitochondrial dysfunction is proposed to be substantially associated with ageing and ageing-related diseases like Alzheimer’s disease (AD). However, it is unclear whether different mouse models with mitochondrial-related diseases have similar changes in mitochondrial morphology of the same tissues. Moreover, whether similarities in mitochondrial morphology can be a suitable marker for screening and/or discovering mitochondrial-protective substances remains unknown. Mitochondria morphology in different tissues of a novel mitochondrial outer membrane protein Slc25a46 knockout mouse and a traditional APPSWE/PS1ΔE9 transgenic mouse were examined using transmission electron microscope (TEM). Both young Slc25a46 knockout mice and aged APPSWE/PS1ΔE9 mice models showed similar mitochondrial damage in cerebellum tissues. The results indicated that different mitochondrial-related diseases shared similar alteration and defects in mitochondrial morphology. Furthermore, Lycium ruthenicum Murr. extract, a bioactive food substance with cognition-improving property, could effectively improve muscle strength and increase body weight in the Slc25a46 knockout mice. These findings suggest that mitochondrial morphology defects in mice models, particularly in the mitochondrial compartment, represent a unified and effective marker for screening and validating natural product-derived functional substances with mitochondrial protective properties. It also holds potential application in mitochondrial-impaired senile neurodegenerative diseases, especially in AD.